The prehospital patient pathway and experience of care with acute heart failure: a comparison of two health care systems. (24th December 2020) - McCambridge, Joseph; Keane, Ciara; Walshe, Myra; Campbell, Patricia; Heyes, James; Kalra, Paul R.; Cowie, Martin R.; Riley, Jillian P.; O'Hanlon, Rory; Ledwidge, Mark; Gallagher, Joseph; McDonald, Kenneth
Abstract: Aims: This study aimed to analyse community management of patients during the symptomatic period prior to admission with acute decompensated heart failure (ADHF). Methods and results: We conducted a prospective, two‐centre, two‐country observational study evaluating care pathways and patient experience in patients admitted to hospital with ADHF. Quantitative and qualitative data were gathered from patients, carers, and general practitioners (GPs). From the Irish centre, 114 patients enrolled, and from the English centre, 50 patients. Symptom duration longer than 72 h prior to hospitalization was noted among 70.4% (76) Irish and 80% (40) English patients, with no significant difference between those with a new diagnosis of HF [ de novo HF (dnHF)] and those with known HF [ established HF (eHF)] in either cohort. For the majority, dyspnoea was the dominant symptom; however, 63.3% (31) of these Irish patients and 47.2% (17) of these English patients did not recognize this as an HF symptom, with no significant difference between dnHF and eHF patients. Of the 46.5% (53) of Irish and 38% (19) of English patients reviewed exclusively by GPs before hospitalization, numbers prescribed diuretics were low (11.3%, six; and 15.8%, three, respectively); eHF patients were no more likely to receive diuretics than dnHF patients. Barriers to care highlighted by GPs included inadequate access to basic diagnostics, specialist support and up‐to‐date patient information, and lack of GP comfort in managing HF. Conclusion: The aforementioned findings, consistent across both health care jurisdictions, show a clear potential to intervene earlier and more effectively in ADHF or to prevent the need for hospitalization.